The CDCAS Framework: Integrating the Stages of Change Model and the INCOME Framework to Inform Treatment of Individuals with a Substance Use Disorder and Disability - Terri Lucas (Journal of Scholarly Engagement)
Employment has been indicated as a contributor to positive outcomes for both people with substance use disorders and those with disabilities. However, there is a disconnect between vocational rehabilitation services and substance use treatment. This paper will present a new theoretical framework for working with individuals with both a substance use disorder and a disability. This new framework (The CDCAS Framework) integrates the Stages of Change Model for working with individuals with addictions and the INCOME framework for working with individuals with a disability to inform a new treatment modality for people with a substance use disorder and a disability.